The Internationalization of Firms: Some Lessons from ASEAN Firms - Mohamad, Mohamad Hanapi (Penerbit Universiti Utara Malaysia, 2016)
In the last 50 years the debate on the development of international business remained unsettled, especially that concerning the establishment of multinational firms from developing countries. Using the Ownership Locational Internalization (OLI) Model this paper examined the formation of multinational firms from ASEAN countries.We found positive similarities in the advancement of the firm’s specific ownership advantages such as skills, management know-how, R&D and technological capabilities. Unlike the firms from developed countries, the firms from developing countries adopted local elements in their products and services.